THE INFLUENCE OF SUBTITLE FILM ON STUDENTS’ LISTENING MOTIVATION - Nur Zahrah Azizah; Muhammad Yaumi (Universitas Islam Negeri Alauddin Makassar, 2018)
This paper is aimed to describe the influence of making subtitle film on students’ listening motivation. The population of this research is the second semester students of English Education Department in academic year 2016/2017. The method used in this paper was a quantitative method with experimental research design. In addition, the research data were collected by using questionnaire. The data were analyzed through Likert scale and descriptive statistics. The result research shows that the mean score of students’ pre-questionnaire is 60.9 from the total score 1462 and the post questionnaire is 65.8 from the total score 1580. The result of analysis indicates that in teaching listening by making subtitle film can increase their listening motivation. It proved by t-test which is higher than t-table.. It also means that there are a significant influence of the use subtitle film in increasing students’ motivation in listening.